PENGARUH MANAJEMEN STRATEGI DAN LINGKUNGAN MASYARAKAT TERHADAP AKHLAKUL KARIMAH ANAK-ANAK PANTI ASUHAN AL-HIKMAH TANAH MAS KECAMATAN TALANG KELAPA KABUPATEN BANYUASIN - Dani Dwi Hidayat; Nurseri Hasnah Nasution; Emi Puspita Dewi (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
The thesis research entitled "The Influence of Strategic Management and Community Environment on the Akhlakul Karimah of the Children of the Al-Hikmah Tanah Mas Orphanage, Talang Kelapa District, Banyuasin Regency" as the background of this research is the lack of exemplary guidance and supervision of orphanage children so that their morals are not yet well formed overall. The purpose of this study was to determine the effect of strategic management on the akhlakul karimah of children at the Al-Hikmah Orphanage. This research uses a type of quantitative research with a survey technique that is carried out by distributing questionnaires or questionnaires. Sampling was carried out using a nonprobability sampling technique, saturated sampling, namely the sampling technique for all members of the population used as a sample, namely 52 people. Data were analyzed by Instrument Test (Validity and Reliability Test), Classical assumption test, Simple linear regression analysis, and Hypothesis Test (t test and Coefficient of Determination Test) using SPSS version 23 software tools. The results of this study indicate that there is an influence of strategic management and the community environment on akhlakul karimah. It is proven that the R Square value in the table is 0.219 which indicates that the akhlakul karimah variable (Y) is influenced by the strategic management variable (X1) and the community environment (X2). of 21.9% and the remaining 78.1% is influenced by other factors not examined.